Empowering Students in Maggot Cultivation at the Jamiyyatul Mubtadi Cibayawak Islamic Boarding School - Syafitri Jumianto; Lusi Anindia Rahmawati; Asep Maksum; Musoffa Musoffa; Aris Machmud (International Journal of Engineering, Science and Information Technology, 2025)
Organic waste management remains a critical global challenge, particularly in developing countries where improper handling contributes to environmental degradation and public health risks. In Indonesia, the dominance of organic waste in landfills presents an opportunity for circular economy practices. This study aims to examine the effectiveness of maggot (Black Soldier Fly/BSF) cultivation as a community-based empowerment strategy to enhance waste management, improve student nutrition, and strengthen economic resilience within an Islamic boarding school environment. This research employed a participatory community-based approach involving 300 students at the Jamiyyatul Mubtadi Cibayawak Islamic Boarding School. The intervention consisted of five main stages: preparation and coordination; socialisation and team formation; technical and managerial training; implementation of appropriate technology; and continuous mentoring and evaluation. Organic waste generated from the school kitchen (approximately 200 kg/day) was partially processed (30–50 kg/day) into maggot biomass, which was subsequently utilised as feed for catfish cultivation. Data were collected through observation, production records, and pre- and post-intervention assessments. The findings demonstrate significant improvements across multiple dimensions. Maggot production increased from approximately 0.5 kg/day to 1.6 kg/day following enhanced waste utilisation and the introduction of supporting technologies such as drying and pelletizing machines. Student participation expanded from 5 to 20 active members in the santripreneur group. Nutritional outcomes also improved, as indicated by increased frequency of fish consumption from once to twice per week and a rise in nutritional knowledge scores from 56% to 82%. Additionally, maggot-based feed production improved in quality, achieving a longer shelf life (up to 3 months) and greater efficiency in aquaculture practices, with catfish survival rates exceeding 80%. The study highlights that integrating maggot cultivation with waste management and aquaculture can effectively support a sustainable circular economy model in educational institutions. Beyond environmental benefits, this approach contributes to improved food security, reduced feed costs (up to 40%), and the development of entrepreneurial skills among students. Despite initial constraints in technology and management capacity, targeted training and infrastructure support proved essential in optimising outcomes. This model demonstrates strong potential for scalability and replication in similar community-based settings.